Reproductive change in Bangladesh: Evidence from recent data - Ruhul Amin; Jamir Chowdhury; Ashraf U. Ahmed; Robert B. Hill; M. Kabir (Asia-Pacific Population Journal, 1993)
The removal of the social, psychic and economic costs of contraception coupled with efforts to ’crytallize’ demand would hasten the fertility decline.